Solution-processed CuZn1−xAlxS2 : a new memory material with tuneable electrical bistability - Jinesh, K. B. (2013)
CuZn1−xAlxS2 (CZAS) thin films deposited by the chemical spray pyrolysis (CSP) technique exhibit reversible electrical bistability in current–voltage measurements. The threshold voltage and current for switching can be tuned by the initial voltage applied to reset the device. X-ray diffraction and high-resolution transmission electron microscopy imaging show that the initial crystal structure of CZAS is similar to CuAlS2 with slightly expanded lattices due to the presence of Zn. The electrical memory effect in this material is observed only when both Zn and Al are present in the film, indicating that migration of interstitial Al towards the anode may be the origin of this memory effect.